2009
DOI: 10.1158/1535-7163.mct-08-1090
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia prevents etoposide-induced DNA damage in cancer cells through a mechanism involving hypoxia-inducible factor 1

Abstract: Intratumoral hypoxia is associated with resistance to therapy in many human cancers, and preexposure of tumor cells to hypoxia confers multidrug resistance. Whereas most anticancer drugs kill proliferating tumor cells by causing DNA damage, a role for hypoxia in the prevention and/or repair of drug-induced DNA damage has not been clear. Using the alkaline comet assay, we provide direct evidence that hypoxia-induced resistance to etoposide in human tumor cells (MDA-MB-231 breast carcinoma and DU-145 prostatic a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 44 publications
0
36
1
Order By: Relevance
“…Our data suggest that HIF-1 α knockdown induced the DDR in cells exposed to 1% hypoxia for 24 h, accompanied by JMJD2B downregulation; furthermore, this change coincided with the suppression of JMJD2B (Figure 2A). It has also been reported that HIF-1 could restrain etoposide-induced DNA damage in hypoxia (Sullivan and Graham, 2009). Thus, it is very likely that HIF-1 α may partially regulate the DDR through JMJD2B.…”
Section: Discussionmentioning
confidence: 94%
“…Our data suggest that HIF-1 α knockdown induced the DDR in cells exposed to 1% hypoxia for 24 h, accompanied by JMJD2B downregulation; furthermore, this change coincided with the suppression of JMJD2B (Figure 2A). It has also been reported that HIF-1 could restrain etoposide-induced DNA damage in hypoxia (Sullivan and Graham, 2009). Thus, it is very likely that HIF-1 α may partially regulate the DDR through JMJD2B.…”
Section: Discussionmentioning
confidence: 94%
“…Third, HIF-1 inhibits expression of pro-apoptotic mitochondrial proteins ( BAX, BID ) and caspases ( CASP3, CASP8, CASP10 ) and induces expression of anti-apoptotic proteins ( BCL2 , BIRC5 ) [8084]. Fourth, HIF-1 prevents chemotherapy-induced DNA damage by inhibiting the expression of topoisomerase IIα protein [85] or the DNA-dependent protein kinase complex [86]. Fifth, HIF-1-dependent metabolic reprogramming [16, 17, 30, 44, 45, 87, 88] may decrease ROS levels and thereby inhibit chemotherapy-induced cell death [89].…”
Section: Can Hif Inhibitors Improve Current Therapies?mentioning
confidence: 99%
“…Many of these HIF-1 inducible genes such as VEGF, Glut-1, MDR, and Bcl-2 directly or indirectly mediate chemoresistance 19 .Therefore, in a wide range of different tumor types, e.g. hepatocellular carcinoma, neuroblastoma, and lung cancer, inhibition of HIF-1α resensitizes cells to drug treatment in hypoxia and is then a valid target to reverse hypoxia-induced drug resistance 8,9,15,19,21,25,[27][28][29][30]56 . HIF-1α accumulation has been associated with shorter survival in patients with early stage cervical, breast, ovarian, endometrial, oropharyngeal squamous cell carcinoma, and oligodendroglioma.…”
Section: Hif-1 and Chemoresistancementioning
confidence: 99%
“…In this context, the most studied transcription factor is hypoxia-inducible factor-1 (HIF-1). HIF-1 is an important factor in the adaptation of cells to hypoxic environments, and significantly contributes to the aggressiveness and chemoresistance of number of different tumours 5,[7][8][9]15,19,21,[25][26][27][28][29][30] . However, these changes can be independent of HIF-1 (ref.…”
Section: Introduction -Hypoxia-induced Chemoresistancementioning
confidence: 99%